The Importance of Natural Disaster Insurance in Indonesia - Laila Sasikirana; Azzahra Nabilla Maisun Syaiim; Fuad Al Mubarok (International Research of Economic and Management Education, 2021)
Insurance is an agreement that has been agreed upon by both parties between the insurer (insurance company) and the insured (someone who buys insurance services). In the agreement, the insured must pay a certain amount of money within a specified time, which is called the premium. Insurance premiums will determine the compensation that will be given. Insurance provides protection from risks that cause them to reduce the risk of loss when an asset is damaged, minimize the impact of unexpected events such as looting or disasters, and minimize the expenditure of large medical funds in the event of an accident on the insured. Indonesia has the potential for natural disasters with a high intensity of natural disasters and has a fairly high potential for losses. The disaster management process regulated in Law Number 24 of 2007 concerning Disaster Management still has weaknesses, namely the absence of a derivative regulation of the disaster management law, not yet optimal support for disaster budgets, the slow mechanism of the disaster management fund process, and slow mitigation and response efforts. disaster emergencies, and weak coordination between relevant agencies. These weaknesses make it longer and the losses incurred increase so that it adds to the burden due to natural disasters.Insurance is an agreement that has been agreed by both parties between the insurer (insurance company) and the insured (someone who buys insurance services). In the agreement the insured must pay a certain amount of money within a specified time, which is called the premium. Insurance premiums will determine the compensation that will be given. Insurance provides protection from risks that cause one of them to reduce the risk of loss when an asset is damaged, to minimize the impact of unexpected events such as looting or disasters, and to minimize the expenditure of large medical funds in the event of an accident to the insured.Indonesia has the potential for natural disasters with a high intensity of natural disasters and has a fairly high potential for losses. The disaster management process regulated in Law Number 24 of 2007 concerning Disaster Management still has weaknesses, namely the absence of a derivative regulation of the disaster management law, not yet optimal support for disaster budgets, the slow mechanism of the disaster management fund process, and slow mitigation and response efforts. disaster emergencies, and weak coordination between relevant agencies. These weaknesses make it longer and the losses incurred increase so that it adds to the burden due to natural disasters.